Possible side effects of ChAdOx1 nCov-19 vaccine in patients with sickle cell disease - Salam Alkindi; Refaat Abdullah Elsadek; Anil V Pathare (Mediterranean Journal of Hematology and Infectious Diseases, 2021)
Vaccines against acute respiratory syndrome Coronavirus 2(SARS-CoV2) are critical weapons to control the spread of the deadly Coronavirus 2019(COVId-19) virus worldwide. Although these vaccines are generally safe, their widespread use has produced reports of rare complications, including vaccine-induced immune thrombotic thrombocytopenia (VIITT), particularly in connection with ChAdOx1 nCov-19. We have identified three cases of sickle cell disease (SCD) experiencing a severe vaso-occlusive crisis (VOC) shortly after the vaccine. Despite being stable for a long time, they had fever with tachycardia, along with a significant rise in WBC, liver enzymes, particularly alkaline phosphate, with a remarkable drop in hemoglobin, and platelets and one of them probably had fatal TTP like syndrome. Given these findings, physicians and patients should exercise caution when taking this type of vaccine and be aware of these safety concerns.